EGFR uncommon alterations in advanced non-small cell lung cancer and structural insights into sensitivity to diverse tyrosine kinase inhibitors - Xu, Haiyan; Yang, Guangjian; Liu, Runze; Yang, Yaning; Li, Weihua; Li, Junling; Hao, Xuezhi; Xing, Puyuan; Wang, Yan (Frontiers in Pharmacology, 2022)
Background：Approximately 10% of patients with non-small cell lung cancer (NSCLC) harbor uncommon epidermal growth factor receptor (EGFR) alterations. This study aims to investigate the therapeutic responses and predict the binding activity of different tyrosine kinase inhibitors (TKIs) for EGFR uncommon alterations. Methods：Between May 2014 and June 2021, clinical outcomes of NSCLC patients harboring EGFR uncommon alterations who received diverse treatment modalities: first-generation (1G) EGFR-TKI, second-generation (2G) EGFR-TKI afatinib, chemotherapy, and 1G TKI in combination with chemotherapy as the initial therapy were retrospectively analyzed, and structural analysis for the binding activity of major uncommon subtypes G719A, S768I and L861Q to different TKIs were predicted. Results：A total of 102 NSCLC patients harboring EGFR uncommon alterations with treatment and survival outcomes were included and analyzed. The majority of patients presented compound mutations (54.9%), and G719X plus S768I was the predominant subtype (n=33, 32.3%). There was a significant difference in median progression-free survival (mPFS) between therapeutic patterns (P=0.015) and EGFR alteration subtypes (P=0.017). Rather than almonertinib and furmonertinib, afatinib, dacomitinib and osimertinib revealed favorable binding activity to G719A mutation. In contrast, S768I and L861Q mutation indicated an unaffected binding activity to these diverse kinds of EGFR TKIs. Conclusions：Together with afatinib, 1G-TKIs combined with chemotherapy might be another effective option for NSCLC patients harboring EGFR uncommon alterations. Based on computational findings, afatinib, dacomitinib, and osimertinib might confer favorable activity to G719A, S768I and L861Q, whereas almonertinib and furmonertinib revealed less activity to G719A.